Prisoner b-3087 ebook - Gratz, Alan (2013)
From Alan Gratz, the #1 New York Times bestselling author of Refugee , comes this wrenching novel about one boy's struggle to survive ten concentration camps during the Holocaust. Based on the inspiring true life story of Jack Gruener. 10 concentration camps. 10 different places where you are starved, tortured, and worked mercilessly. It's something no one could imagine surviving. But it is what Yanek Gruener has to face. As a Jewish boy in 1930s Poland, Yanek is at the mercy of the Nazis who have taken over. Everything he has, and everyone he loves, have been snatched brutally from him. And then Yanek himself is taken prisoner — his arm tattooed with the words PRISONER B-3087. He is forced from one nightmarish concentration camp to another, as World War II rages all around him. He encounters evil he could have never imagined, but also sees surprising glimpses of hope amid the horror. He just barely escapes death, only to confront it again seconds later. Can Yanek make it through the terror without losing his hope, his will — and, most of all, his sense of who he really is inside? Based on an astonishing true story.